A STUDY ON THE SECOND YEAR STUDENTS’ ABILITY OF SMP AS-SHOFA PEKANBARU IN CONSTRUCTING YES/NO QUESTIONS - Afrihas, Najmi Afrihas; Prawati, Atni Prawati; Nababan, M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was about the ability of the students in constructing yes/no questions. The aim of this research was to find out the ability of the second year students of SMP As-Shofa Pekanbaru in constructing yes/no questions. The population was 138 students. The sample was chosen through cluster random sampling and lottery technique. The analysis was based on giving test to the students. It was found that 20 out of 138 students were 1 student (5%) in excellent level, 5 students (25%)in good level, 10 students (50%) in mediocre level, 2 students (10%) in poor level and 2 students (10%) in very poor level. The mean score of the students was 51,81. It implies that the students’ ability falls into mediocre ability level. Based on the result, it is recommended that teachers should pay attention more on material yes/no questions escpecially in using did.Key Words: Ability, Constructing, Yes/No Questions.